An Analysis of Centralized Control on SB.02 Feed Recloser to Reduce the Length of Outage Hours at PT PLN (Persero) ULP Sibolga City - Donny Ferdian Hutahuruk; Solly Aryza; Hamdani, Hamdani (Sean Institute, 2024)
This study aims to analysed the effectiveness of centralized control on the SB.02 feeder recloser at PT PLN (Persero) ULP Sibolga in reducing outage duration. Outage du-ration is a key indicator in evaluating the reliability of the electricity distribution system, directly impacting service quality and customer satisfaction. Currently, the recloser on the SB.02 feeder is manually controlled, which extends the response time to disturbances and contributes to prolonged outages. By implementing centralized control on the re-closer, disturbance detection and handling times are expected to improve, resulting in reduced outage duration. The research method involves collecting data on disturbances, outage duration, and comparing outage hours before and after implementing centralized control. Testing is conducted through simulation and analysis of operational data over a specific period. The analysis results indicate that centralized control can significantly shorten recovery times, thus reducing total outage hours. In conclusion, implementing centralized control on the SB.02 feeder recloser can improve the reliability of the electric-ity distribution system at ULP Sibolga, minimizing the negative impacts of network dis-turbances on customers. The study recommends adopting centralized control on other feeders to enhance operational efficiency and service quality at PT PLN (Persero).